Developing and Validating a Holistic Islamic Religiosity Scale: Evidence from Indonesian Islamic Banking Consumers - Wenda Wahyu Christiyanto; Vanessa Gaffar (SHAHIH: Journal of Islamicate Multidisciplinary, 2026)
Religiosity has been widely recognized as an important determinant of consumer attitudes and behavior. However, existing measures are often developed within non-Islamic contexts or focus on specific aspects of Muslim religiosity, resulting in limited consensus regarding a comprehensive measure grounded in Islamic teachings. In particular, there remains a lack of validated instruments that integrate the foundational Islamic concepts of iman (faith) and taqwa (piety) into a holistic construct suitable for contemporary Muslim consumer contexts. This study aims to develop and validate a new construct, namely Holistic Islamic Religiosity, among Islamic banking consumers in Indonesia. A mixed-method sequential exploratory design was employed, utilizing a Systematic Literature Review of 76 selected articles in the qualitative phase, followed by a quantitative survey of 403 customers analyzed via Exploratory Factor Analysis and Confirmatory Factor Analysis. The findings demonstrate that Holistic Islamic Religiosity comprises two interrelated dimensions: Faith (four indicators: belief in God, the importance of religion, its influence on life, and social responsibility) and Piety (three indicators: ritual worship, daily supplication, and avoidance of sinful behavior). The model exhibits satisfactory validity and reliability, contributing a theoretically grounded instrument for future research in Islamic banking, finance, marketing, and halal tourism.